Clara cell 16 KDa protein mitigates house dust mite-induced airway inflammation and damage via regulating airway epithelial cell apoptosis in a manner dependent on HMGB1-mediated signaling inhibition - Meixuan Liu; Jingjing Lu; Qian Zhang; Yunxuan Zhang; Zhongliang Guo (BMC, 2021)
Abstract Background House dust mite (HDM) inhalation can cause airway epithelial damage which is implicated in the process of airway inflammation in asthma. High mobility group box 1 (HMGB1) is critically required for cellular damage and apoptosis as an important endogenous danger signal. Recently, Clara cell 16KDa protein (CC16) has been identified to exert anti-inflammatory and immunomodulatory influence in various injury-related diseases model. However, little is known about its ability to protect against airway epithelial injury in allergic asthma. This study was aimed to clarify the protective roles of CC16 on airway epithelia in HDM-induced asthma and the regulation of HMGB1 by CC16. Methods Mice were sensitized and challenged by HDM extract and administrated intranasally with CC16 (5 μg/g or 10 μg/g) or saline in the challenged period. The BEAS-2B human airway epithelial cell line were cultured with CC16 or the control vehicle and then exposed to HDM. Knockdown or overexpression of HMGB1 was induced by cell transfection or intratracheal injection of recombinant adenovirus. Results CC16 treatment decreased airway inflammation and histological damage of airway epithelium dose-dependently in HDM-induced asthma model. Airway epithelia apoptosis upon HDM stimulation was noticeably abrogated by CC16 in vivo and in vitro. In addition, upregulation of HMGB1 expression and its related signaling were also detected under HDM conditions, while silencing HMGB1 significantly inhibited the apoptosis of BEAS-2B cells. Furthermore, the activity of HMGB1-mediated signaling was restrained after CC16 treatment whereas HMGB1 overexpression abolished the protective effect of CC16 on HDM-induced airway epithelia apoptosis. Conclusions Our data confirm that CC16 attenuates HDM-mediated airway inflammation and damage via suppressing airway epithelial cell apoptosis in a HMGB1-dependent manner, suggesting the role of CC16 as a potential protective option for HDM-induced asthma.